Ritual Dance as a form of Worship - a Case of Bharata Nāṭyam - Mickevičienė, Diana (Acta Orientalia Vilnensia, 2004)
The article focuses on the nature of the Bharata Nāṭyam style of classical Indian dance as a form of worship, analyzing its relation with the environment of a Hindu temple. Linear parallels are drawn between the traditional repertoire of the Bharata Nāṭyam recital and the process of going to the temple. The ontological relation between the dance and the temple as well as the link between the internal space of the dance and that of the temple are also analyzed.